Fractional Minkowski-Type Integral Inequalities via the Unified Generalized Fractional Integral Operator - Tingmei Gao; Ghulam Farid; Ayyaz Ahmad; Waewta Luangboon; Kamsing Nonlaopon (Journal of Function Spaces)
This paper is aimed at presenting the unified integral operator in its generalized form utilizing the unified Mittag-Leffler function in its kernel. We prove the boundedness of this newly defined operator. A fractional integral operator comprising a unified Mittag-Leffler function is used to establish further Minkowski-type integral inequalities. Several related fractional integral inequalities that have recently been published in various articles can be inferred.